BIAS IDEOLOGI, MAZHAB, DAN KEYAKINAN DALAM TERJEMAHAN AL-QUR’AN - Hasbi Maulana (STAI Dirosat Islamiyah Al-Hikmah Jakarta, 2026)
The translation of the Qur’an occupies a vital role in conveying the message of divine revelation to Muslim communities across different languages and cultures. However, Qur’anic translation is never a purely neutral linguistic exercise, as translators inevitably carry ideological, jurisprudential, and doctrinal backgrounds that shape their interpretive choices. This study aims to examine and analyze the forms of ideological, mazhab-based, and belief-related bias that appear in Qur’anic translations, with particular attention to their implications for religious understanding. This research employs a qualitative approach through library research, utilizing descriptive-analytical methods and drawing on theories of translation ideology, comparative fiqh, and Islamic hermeneutics as analytical frameworks. The results reveal three distinct categories of bias. Ideological bias is evident in the Indonesian Ministry of Religious Affairs translation, where the term jihad is rendered broadly to reflect a moderate Islamic orientation. Mazhab-based bias appears in the verse of wudu (QS. Al-Ma’idah: 6), where different jurisprudential schools interpret the phrase wa arjulakum divergently, producing varying rulings on washing or wiping the feet. Belief-related bias is evident in the translation of ahl al-bayt (QS. Al-Ahzab: 33) and the verb istawa (QS. Taha: 5), rendered differently by Sunni and Shi’a traditions and by Salafi and Ash’ari theological orientations. This study concludes that Qur’anic translation is fundamentally an interpretive act shaped by the translator’s worldview, and that recognizing these biases is essential for readers to engage critically with translations and appreciate the diversity of Islamic scholarly tradition.